(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
Fish and fish products can support 40% of world diets, which meets 60% of the animal protein requisites in Bangladesh. Infections of fishes, along with the continuously elevated emergence of microbial resistance, are the major drawbacks to the massive milestone forward. This investigation aimed to reveal the antimicrobial resistance patterns of the pathogens associated with diverse fish infections. According to Bergey’s manual of bacteriological classification, isolated pathogens were provisionally identified at genera levels based on their cultural, morphological, and biochemical characteristics. The Kirby-Bauer (Cockerill and CLSI, 2013) disc diffusion method was exploited to determine the antimicrobial resistance. Pathogenic growths were found in 150 (83.34%) out of 180 samples by Aeromonas spp. (39.33%), Vibrio spp. (16.67%), Flavobacter spp. (14.67%), Edwardsiell spp (12.67%), Pseudomonas spp. (9.33%), Streptococcus spp. (5.55%), and Citrobacter spp. (2%) in Shing (Heteropneustes spp.), Pangus (Pangasius spp.), Pabda (Ompok spp.), Gulsha (Mystus cavasius), Tilapia (Oreochromis niloticus), Koi (Cyprinus spp.), Magur (Clarias batrachus), and Tengra (Mystus tengara). Pathogens showed resistance against Amoxicillin (136/150; 90.67%), Chlortetracycline (135/150; 90%), and Erythromycin (134/150; 89.33%), whereas Levofloxacin (138/150; 92%), Ciprofloxacin (123/150; 82%), Neomycin (120/150; 80%), and Colistin (117/150; 78%), exhibited potential effectiveness. A huge frequency of 60% (90 out of 150) of pathogens exhibited as high as 21 antimicrobial resistance patterns towards a minimum of 4 antibiotics and a maximum of 8 antibiotics, whereas Aeromonas spp. isolates were the most prominent. The investigation would provide substantial guidance to veterinarians and animal husbandmen involved in fish cultivation to design therapeutics against infections. Regular and vigorous investigation and implementation of the acquired knowledge would be the only possible solution to halt the rapid increase of antimicrobial resistance. J. Bangladesh Acad. Sci. 48(1); 61-74: June 2024